ISSUES OF MINIMAL SOCIAL STANDARDS AND GUARANTEES - Zhakupov Руслан Елюбаевич; Khassenov Муслим Ханатович (Scientific and legal journal «Bulletin of the Institute of Legislation and Legal Information of the Republic of Kazakhstan», 2014)
The present article is devoted to conceptual approach to minimal social standards and guarantees in order to optimal and effective legislative enforcing of their substance.